ANALISIS PENGENDALIAN PERSEDIAAN OBAT BERDASARKAN METODE ABC, EOQ DAN ROP - Anna Fitrotun Nisa (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
In the supply of medicines in the pharmacy warehouse of Muhammadiyah Gresik Hospital, there has been drug void and expired date. This research was conducted by using descriptive qualitative research approach. Based on the analysis of ABC, the use of drugs in group A was 43 drugs or 7.75% of all drug supplies with 90323 items or 69.59% of total drug usage. Medicines belonging to group B are 78 types of drugs or 14.05% of all types of drug supplies with the amount of use as much as 26371 items or 20.32% of total drug usage. While the drugs that include group C as much as 434 types of drugs or 78.25% of all types of drug supplies with the amount of use as much as 13103 items or 10.09% of total drug usage. Based on analysis of ABC Investment classified as A is as much as 78 types of drugs or 14.5% of all drugs with an investment of Rp 250,733,719.00 or 69.28% of the total drug investment. The drugs belonging to group B are as many as 135 types of drugs or 24.32% of all drugs with an investment value of Rp 82,624,061.00 or 22.83% of the total drug investment. While the drugs belonging to group C are as many as 342 types of drugs or 61.63% of all drugs with an investment of Rp 28,513,928.00 or 7.89% of the total drug investment. Based on EOQ analysis then the optimum order amount from Group A with high investment value varies from 1-2565 items. While according to ROP analysis obtained point reorder/time reorder for 78 drugs that belong to group A with high investment value varies from 1-2861 item.